2018
DOI: 10.3389/fmicb.2018.00566
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outbreak of Healthcare-Onset Healthcare-Associated Clostridioides difficile Infections Among Intensive Care Patients in a Large Teaching Hospital in China

Abstract: Background: Clostridioides difficile infection (CDI) is an important cause of morbidity and mortality among hospitalized patients. In China, however, hospital staff do not routinely test for CDI, leading to under-diagnosis and poor patient outcomes. Locally generated CDI data can help assess the magnitude of the problem and strengthen approaches for CDI prevention and control.Methods: We prospectively monitored hospital-onset hospital-associated (HOHA) CDI in four intensive care units (ICUs) from June 2013 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
9
4
Order By: Relevance
“…In our study, we found that the prevalence of CDI was 4.12%, and much higher than that in most studies reported from European countries [27]. Furthermore, 28.7% of ICU patients with diarrhea developed CDI, which was much higher than the 8% reported in another Chinese study [28]. Meanwhile, the detection rate of CDC in our study was 3.12%, and relatively lower than the 7% reported in a retrospective study from Kuwait [29].…”
Section: Discussioncontrasting
confidence: 79%
“…In our study, we found that the prevalence of CDI was 4.12%, and much higher than that in most studies reported from European countries [27]. Furthermore, 28.7% of ICU patients with diarrhea developed CDI, which was much higher than the 8% reported in another Chinese study [28]. Meanwhile, the detection rate of CDC in our study was 3.12%, and relatively lower than the 7% reported in a retrospective study from Kuwait [29].…”
Section: Discussioncontrasting
confidence: 79%
“…In our study, we found that the prevalence of CDI was 4.12%, much higher than most studies reported in European countries [27]. And 28.7% of the patients with diarrhea in ICU developed CDI which was much higher than the 8% reported in another Chinese study [28]. As for CDC, the detection rate of CDC in our study was 3.12%, relatively lower than the 7% reported in a retrospective study in Kuwait [29].…”
Section: Discussioncontrasting
confidence: 73%
“…Vancomycin and metronidazole have long been used as first-line drugs for the treatment of CDI [21, 22]. In this study, one isolate displayed high-resistance to vancomycin (MIC> 8 μg/ml).…”
Section: Discussionmentioning
confidence: 80%